Comparative study of the retinal structure and visual acuity in 7–12-year-old children between children with a history of treatment of retinopathy of prematurity and regressed retinopathy of prematurity: multicenter review of J-CREST - Yutaro Mizusawa; Tomo Nishi; Nahoko Ogata; Kayo Shinomiya; Yoshinori Mitamura; Naoki Kimura; Fumi Gomi; Akiko Miki; Makoto Nakamura; Takamasa Kinoshita; Shumpei Obata; Masahito Ohji; et al. (BMC Ophthalmology)
Abstract Purpose Previous studies have reported the efficacy of photocoagulation (PC) therapy for treating retinopathy of prematurity (ROP); however, its long-term effects on visual function and retinal structure remain unclear. This study compared the visual function and retinal structure of school-aged children (7–12 years) with ROP who underwent PC therapy with those of children with untreated ROP. Methods Seventy-eight eyes of 78 patients diagnosed with ROP who were followed up until school age were evaluated. Fifty-one eyes that underwent PC therapy and 27 eyes with spontaneously regressed ROP were included in the PC-treated and untreated groups, respectively. One eye of each patient was included in the analysis at random. Results The mean best-corrected visual acuity (BCVA) in the PC-treated and untreated groups was 0.05 ± 0.19 and 0.04 ± 0.35 logarithm of the minimum angle of resolution (logMAR) units and no significant differences were observed (p = 0.896, t-test). The mean spherical equivalent in the PC-treated and untreated groups was − 4.2 ± 4.7 D and − 0.8 ± 2.5 D (p < 0.001). PC-treated eyes were treated at ROP zone II in 42/51 eyes, ROP stage 3 in 41/51 eyes and showed plus disease in 31/51 eyes. Untreated eyes were regressed from ROP zone II in 22/27 eyes, ROP stage3 in 8/27eyes, and showed plus disease in 3/27eyes. The eyes in the PC-treated group were more myopic than those in the untreated group; further, they exhibited a unique foveal morphology with thicker foveal thickness (274.2 ± 29.9 μm in the PC-treated and 239.9 ± 25.0 μm in the untreated groups p < 0.001), inner retinal layer retention (23.6 ± 12.5 μm in the PC-treated and 14.1 ± 7.1 μm in the untreated groups p = 0.004) and a thicker outer nuclear layer (130.3 ± 20.0 μm in the PC-treated and 110.8 ± 20.6 μm in the untreated groups p < 0.001). No significant differences were observed in the outer retinal, inner segment (43.7 ± 4.9 μm in the PC-treated and 45.2 ± 5.0 μm in the untreated groups p = 0.231), or outer segment (45.0 ± 4.6 μm in the PC-treated and 43.8 ± 4.8 μm in the untreated groups p = 0.238) layers’ thickness. Conclusion The findings of the present study suggest that school-aged children who underwent PC therapy for ROP had good visual acuity, however the inner retinal structure remained immature.